Analysis of Corruption Behavior and Good Government Governance - Nasution, Dito Aditia Darma; Sianipar, Martin Yehezkiel; Welly, Yerisma (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The regional government system is always improving from time to time in order to realize good regional government for all people in the region. Regional governments have made efforts to realize good government governance through policy making. For various reasons, good government governance is considered an ideal concept to be implemented in local government. This research aims to analyze corrupt behavior in local government, especially in Aceh, and analyze good government governance in Aceh. This research method uses qualitative descriptive analysis with a literature review approach. We analyze the phenomenon of corruption conditions in Aceh based on document data combined with concepts and expert studies. The research results show that corruption in Aceh involves office holders at the regional level. Apart from that, what is more worrying is that corruption can even penetrate law enforcement, which is supposed to be the enforcer of justice. The emphasis on community participation in regional government is in line with the democratic system implemented in Indonesia. The community's contribution to regional government will certainly have a good impact on regional government itself. Regional government efforts to realize good government governance are carried out by implementing bureaucratic reform, implementing bureaucratic reform both in terms of institutions, procedures and human resources. Apart from that, another regional government effort in implementing good government governance is information disclosure.